Human papillomavirus-related small cell carcinoma of the oropharynx: a case report and literature review. Issue 1 (December 2017) - Bonomi, Marcelo; Ahmed, Tamjeed; Warner, David; Waltonen, Joshua; Sullivan, Christopher; Porosnicu, Mercedes; Batt, Katharine; Ruiz, Jimmy; Cappellari, James
Abstract Background Small cell carcinoma (SCC) is a rare variant of head and neck cancer characterized by a high-grade neuroendocrine cancer with similar features to small cell lung carcinoma (SCLC). Human papillomavirus (HPV) is an increasingly recognized cause of head and neck cancer but usually associated squamous cell carcinoma of the oropharynx. In this report, we present the clinical presentation, diagnosis, and management of a patient with HPV-related SCC of the oropharynx that responded favorably to chemotherapy with cisplatin plus etoposide and concomitant radiation therapy, a regimen typically used in SCLC. Case presentation We present a rare case of a 56-year-old man who presented with a three-month history of an enlarging left-sided neck mass. Imaging was consistent with a soft tissue density at the left tongue base, left level IIB nodal conglomerate, and multiple bilateral cervical lymph nodes, without evidence of distant metastasis. The patient underwent a core biopsy of the left neck level II node which read as a poorly differentiated neuroendocrine carcinoma consistent with small cell carcinoma. Polymerase chain reaction revealed that the tumor was positive for HPV16. The tumor was staged T1N2cM0 (stage IVA). He went on to receive four cycles of cisplatin and etoposide. On cycle two, he started radiotherapy to the oropharynx and involved neck nodes. He received a dose of 70 Gray (2 Gy/fraction) over a seven week-period. During the concomitant phase of chemo-radiation, the patient experienced grade IV mucositis, grade II nausea, and dehydration for which he received additional outpatient fluid and electrolyte replacement. Three months after completion of therapy, a PET/CT showed complete resolution of the tumor and metastatic lymph nodes along with no evidence of distant metastasis. Conclusion Patients with HPV-related cancer of the oropharynx require identification of the small cell variant to optimize therapy and improve outcomes.